African businessmen : a study of entrepreneurship and development in Kenya - Marris, Peter; Somerset, H. C. A. (London : Routledge & K. Paul, 1971)
The development of African entrepreneurship in Kenya is viewed as an aspect both of economic progress and the redistribution of power. The survey covered 87 businesses supported by the Industrial and Commercial Development Corporation, 848 African businesses in market centres up and down Kenya, a study of one location in Nyeri district (prosperous tea and coffee growing area), and 281 Asian businesses in and around Nairobi. Starting with a history of the development and business in one rural community, Mahiga, from precolonial times, it is shown how creative ventures have arisen from a complex of social, economic and historical circumstances, which determine the kind of man who seek out these opportunities, their patterns of organization and their business creed.
Includes index bibliographical references: p. 280-281.
lje 17/1/18
Loans
Keywords: Businesspeople; Entrepreneurship; Kenya